KETIMPANGAN DISTRIBUSI PENDAPATAN ANTARWILAYAH DI PROVINSI SUMATERA UTARA TAHUN 2001 -2016 - Elvis Purba; Ayu Handayani Siregar (Visi Sosial Humaniora, 2020)
This paper decribes how the inequality of income distribution in the Province of North Sumatra Province is based on analysis interregional, namely the West Coast, Nias Islands, the Highlands, and the East Coast. The data analyzed is the Gini coefficient published by BPS North Sumatra Province from 2001 to 2016. Based on the distribution criteria of income from the Gini coefficient, there are three qualitative measures of inequality, viz: (1) relatively evenly distributed (very low inequality), (2) moderate inequality, (3) very high inequality. The results of data analysis show that: (1) there is no one regency or city whose income distribution is classified aa very high inequality, (2) all of regencies and cities in the highlands show a very low inequality, (3) in general, the distribution of income in regencies and cities in the West Coast, Nias Islands and the East Coast is relatively evenly distributed, (4) there is no clear pattern or fully unidirectional correlation between high economic growth rates and an increasingly unequal distribution of income in each regency or city. Very low inequality can also occur in regencies or cities whose economic growth rate are higher than the provincial economic growth rate. Vice versa, there are regencies or cities that have economic growth rates are lower than the provinces but instead show a moderate inequality.